Determining Tourist Visits and Economic Valuation of Natural Attraction of Tretes Waterfall of Wonosalam - Purbowo Purbowo; Ahsin Daroini (Agriscience, 2021)
The aims of the research to analyse the determinant of visits frequency and economic valuation of natural attractions of the Tretes waterfall. Two analysis methods are used by combining the negative-binomial and travel cost method (TCM) with an individual approach. The result showed that independent variables such as total travel expense, age, income, motivation, sex, and duration of enjoying tour partially do not significantly affect visits frequency. The only one independent variable which significantly toward visits frequency is distance. It means closer more often to visit.  The amount of willingness to pay is IDR 50,000 with individual consumer-surplus is IDR 27,397.26, and economic value IDR 328,767,120 per year.